Clinical and Survival Insights into Carcinoma Penis: A Retrospective Analysis at a Tertiary Care Facility - Swain, Santosh Kumar; Moharana, Lalatendu; Biswas, Ghanashyam; Samantaray, Lipsita; Dubey, Ayush; Singhal, Reetu; Inimerla, Bhavya; Sanyal, Antara; Mohanty, Swati Sucharita; Panda, Soumya Surath (South Asian Journal of Cancer, 2025)
The main objective was to evaluate key survival results, comprising progression-free survival (PFS) and overall survival (OS), in individuals with histopathologically confirmed penile cancer, along with an assessment of clinical features, treatment strategies, and therapy-related side effects.This study comprised retrospective analyses of individuals diagnosed with penile cancer, confirmed by histology, between April 2021 and December 2024, regardless of disease stage. Case records were reviewed to gather information on demographics, clinical details, histopathology, and treatment outcomes.As the data was collected retrospectively, no prior sample size estimate was performed. Data analysis was carried out using SPSS version 27.The most common presenting symptoms were ulcerative-proliferative growth (60%), pain (50%), dysuria (40%), and lymphedema (40%). The median age of patients in this retrospective study was 56 years (interquartile range: 49.25–59.25). Out of the 10 patients included, 9 (90%) had localized or locally advanced disease and underwent primary surgical treatment. Among them, eight patients (80%) had partial penectomy, while one patient (10%) underwent total penectomy. These patients received adjuvant chemotherapy and/or radiotherapy based on their disease stage. One patient (10%) had metastatic disease at diagnosis and was treated with upfront palliative chemotherapy. Most patients presented with advanced-stage tumors, with 60% having T3/T4 disease and 90% showing lymph node involvement (N + ). For those with nonmetastatic disease, the median disease-free survival was 14 months (95% confidence interval [CI]: 12.61–15.38). Following disease progression, patients were treated with palliative intent, achieving a median PFS of 12 months (95% CI: 11.29–12.71) and a median OS of 28 months (95% CI: 24.9–31.09). Two patients (20%) experienced grade 3 or higher neutropenia, and one patient had hypothyroidism.In India, penile cancer is frequently identified at an advanced stage. Patients presenting with recurrent, metastatic, or nodal disease tend to have poor OS, even with optimal palliative systemic therapy. This highlights a significant unmet need for more effective systemic treatment options in this group. Our study underscores the pressing need for region-specific research and improved access to multidisciplinary care.
Keywords: clinical profile; survival; carcinoma penis; overall survival; disease-free survival; progression-free survival